The Guru as Śiva: Govinda Kaula’s Gurustutiratnāvalī and a Lineage of Devotion in Kashmir - Stainton, Hamsa (Indo-Iranian journal, 2021)
Abstract This article introduces and analyzes the Gurustutiratnāvalī, a sophisticated eighteenth-century Sanskrit hymn composed by Govinda Kaula of Kashmir in praise of his teacher’s teacher, the prolific author Sāhib Kaula. It evaluates the evidence for Govinda Kaula’s dating, lineage, and literary activity and presents the first published edition and translation of select verses of his Gurustutiratnāvalī based on four manuscripts. The analysis of the hymn focuses on the ways the author equates a specific guru in his lineage—Sāhib Kaula—with the supreme deity Śiva. Using this hymn as a starting point, the article considers the history of guru-praise (gurustuti) and guru-devotion (gurubhakti) in Kashmir as well as in South Asia more broadly. Lastly, it suggests that further work on this lineage and the religious dynamics of the eighteenth and nineteenth century will prove crucial for helping us understand the emergence of what came to be popularly known as “Kashmir Śaivism.”